A comparative study of the structural, magnetic and electrochemical properties of Al3+ and Cu2+ substituted NiZn ferrite/reduced graphene oxide nanocomposites. Issue 17 (1st December 2017) - Meng, Fanbin; Yang, Mo; Zhao, Lei; Zhang, Yujie; Shang, Xueni; Jin, Peng; Zhang, Wei
Abstract: NiZn ferrite/reduced graphene oxide (Ni0.8 Zn0.2 Fe2 O4 /rGO) nanocomposite and Al 3+ and Cu 2+ substituted NiZn ferrite/reduced graphene oxide (Ni0.8 Zn0.2 Al0.1 Fe1.9 O4 /rGO and Ni0.6 Cu0.2 Zn0.2 Fe2 O4 /rGO) nanocomposites were directly synthesized by one-step hydrothermal route. XRD and FTIR confirmed the formation of Ni0.8 Zn0.2 Fe2 O4 /rGO, Ni0.8 Zn0.2 Al0.1 Fe1.9 O4 /rGO and Ni0.6 Cu0.2 Zn0.2 Fe2 O4 /rGO nanocomposites. The average crystallite size was found to be 16.9–20.4 nm. The substitution of Al 3+ /Cu 2+ for Fe 3+ /Ni 2+ ions promotes a variation in unit cell due to the difference of ionic radius between Al 3+ /Cu 2+ and Fe 3+ /Ni 2+, which leads the lattice parameter to vary from 8.353Å to 8.394 Å. Magnetic measurements reveal the saturation magnetization to vary with the replacement of Al 3+ /Cu 2+ for Fe 3+ /Ni 2+ ions. The variations of saturation magnetization in Al and Cu substituted NiZn ferrite/reduced graphene oxide nanocomposites have been explained in the light of Neel's two-sublattice theory. A maximum specific capacitance of 136.91 F/g and energy density of 16.80 W h/kg were obtained in Ni0.8 Zn0.2 Al0.1 Fe1.9 O4 /rGO nanocomposite at a current density of 1 A/g. The enhanced electrochemical performances could be related to the high electronic conduction of Ni0.8 Zn0.2 Al0.1 Fe1.9 O4 /rGO nanocomposite.